CFD analysis of turbulent flows transported by centrifugal pumps under low Re numbers (2020)
Numerical methodologies have presented an inexpensive solution of laminar and turbulent flows capable of predicting a wide range of mechanical devices in science and engineering. Computational tools have been employed in recent years to analyze the conservation equations behavior used to describe the interaction between turbulent and laminar flows used to transfer the energy needed to perform a complex mechanical system. Due to the above, this paper purpose the application of the numerical method linked to mathematical algorithms capable of generating an approximated solution of the partial differential equations system which determines pressure, and velocity values related to the centrifugal pump performance under low Re conditions in a virtual environment through OpenFOAM software, and Salome 8.3.0. An independence mesh analysis was computed to study the computational effort required to establish an approximated turbulence phenomena description performed by the centrifugal pump into the virtual environment supported by MRFSimpleFoam solver. Keywo